Production of TiO2 Nano-Rods Using Combination of Sol-Gel and Electrophoretic Methods - Nosrati, Hassan; Shafi Hosseini, Mehran; Nemati, Mohammad; Samariha, Ahmad (Asian Journal of Chemistry, 2013)
Nano-rods of titanium dioxide have been developed by electrophoretic deposition in polycarbonate templates with 180 nm diameter. Characteristics of the produced nanostructures have been investigated in terms of microstructure, morphology, phase composition, thermal behaviour and chemical bindings using scanning electron microscope, X-ray diffraction and Fourier transform infra red. Scanning electron microscope micrographs demonstrated that the TiO2 nano-rods have grown completely directional with thoroughly similar diameter. In addition, X-ray diffraction analysis revealed that the developed nano-rods have yielded a mixture of anatine and rutile structures after annealing at 530 ºC for 50 min.